Ezra-Nehemiah - Appler, Deborah Ann (Wisdom commentary, 2025)
"Deborah Appler and Terry Ann Smith offer a sustained investigation and feminist critique of Ezra-Nehemiah that moves beyond traditional historical and theological interpretations. Their intersectional analysis engages themes of gender, power, economics, and social justice and demonstrates how ancient and modern communities grapple with community formation and identity amidst ever-evolving social and cultural challenges"--